Catering Management System / Izzuddin Ibrahim - Ibrahim, Izzuddin (2014)
People are busy and excited to make an event. But they do not know where to start it first because it takes a lot of time to prepare and planning to get successful event. Catering Management System in this module is a web based system which provide ordering, booking, and billing. This system is to analyze the problems of customer and caterer. It will avoid the caterers to get confused with the customer order and for customer give easy for them to make ordering and booking either food or equipment. Catering Management System is to develop an online ordering system and construct online menu information. Using guidelines or other method is important to manage the system that we build like this system used agile method and Yii language. It brings easier for customer make the order and for caterer easy to handle the system when it is completed